A New Wind Tunnel Facility Dedicated to Sports Technology Research and Development. (2016) - Bäckström, Mikael; Carlsson, Peter; Danvind, Jonas; Koptyug, Andrey; Sundström, David; Tinnsten, Mats
Abstract: It is desirable to test sportswear and sports equipment at exactly the same conditions experienced during use. Although outdoor tests are in many cases the most adequate, they are at the same time quite complex, demand special measurement technology and wearable equipment. Results of such tests are often hard to interpret due to large variations because of rapidly varying ambient conditions and individual specifics of human objects, among other factors, which are hard or impossible to control. One common alternative is provided through indoor tests made in a stable, controlled environment. Controlling such parameters as temperature, wind speed and direction, air humidity with indoor facilities intended to replicate ambient conditions, and designed to house large objects, is a complex undertaking. Furthermore, replicating seasonal conditions complicates matters even more. A significant amount of research and development related to the operation of sports and other related equipment at high speeds and windy conditions has been carried out in wind tunnels with different degrees of climatic realism. However, the majority of such facilities are designed and constructed for the automotive industry, the aerospace industry and for marine research. A new wind tunnel facility, opened in March 2015 at the Sports Tech Research Centre at Mid Sweden University, is currently among the very few facilities in the world designed under the direct control of sports technology specialists and dedicated primarily to research and development within sports, outdoor clothing and footwear as well as equipment development and testing. The main goal when constructing this dedicated facility has been to successfully replicate ambient conditions for training and equipment testing in environments with controlled wind speed, temperature (+4 to +35 °C) and precipitation (from fine mist to heavy downfall). The wind tunnel facility houses the largest moving belt in Sweden (5 m long and 2.7 m wide) which can be adjusted for leveled, uphill and downhill motion. The moving belt is placed in a 10 m 2 test section in which the wind speed can be adjusted to match belt speed or independently up to 55 km/h (without narrowing the test section). A fog and rain system, mounted in the test section, can generate rainy conditions varying from fine mist to heavy monsoon. It is also possible to open the facility in order to allow experiments to be performed in wide range of outdoor, ambient conditions. This paper presents the basic parameters of the new wind tunnel facility. As this facility is open for wider international cooperation, we also report the general directions of current research and the future work planned to be carried out at this facility.